Heat Transfer Characteristics and Reynolds Stress Budgets in Single-Rib Mounting Channel - Takahiro MIURA; Koji MATSUBARA; Atsushi SAKURAI (Journal of Thermal Science and Technology, 2010)
Heat transfer and fluid flow in a single-rib mounting channel were investigated by directly solving Navier-Stokes and energy equations. Flow and thermal fields were considered to be fully developed at the inlet of the channel, and the simulation was made for spatial advancement of turbulent heat transfer. Keeping the frictional Reynolds number, Reτ0, at 150, the rib height ratio was changed in four steps from H/δ = 0.05 to H/δ = 0.4. Computational results were confirmed to be nearly independent of grid meshes. In addition, numerical accuracy was confirmed through close agreement between computed mean pressure and the experiment by Yao et al. (1995). The numerical results revealed that the highest value of the mean Nusslet number was as large as 1.3 times the smooth surface consuming the same pumping power, and the local enhancement of heat transfer was correlated with the turbulence increase near the rib front and the reattachment point. According to the Reynolds stress budgets for H/δ = 0.2, there were mechanisms to induce powerful fluctuations: (1) Streamwise fluctuation was increased through production by flow deceleration in the upstream of the rib; (2) Redistribution to wall-normal and spanwise fluctuations was fortified by the fluid splattering to the rib front. Therefore, excellent performance of heat transfer was concluded to occur due to flow structures, which induce the strong disturbance near the rib front triggering smooth transition of the separated shear layer.